SPEECH THERAPY IN THE ORAL STIMULATION OF PRE-TERM NEWBORN: EXPERIENCE REPORT - Baratinha de Oliveira, Elivelton; Gomes Damasceno, Lídia; Evandro Brito de Leão, Rômulo (Health and Society, 2022)
Prematurity is one of the main causes of risk factors for Newborns (NBs), as it actively affects the development of newborns and its complications, often resulting in the inability to provide breastfeeding in the first days of life. Therefore, the present study aims to portray the speech therapy assistance to preterm newborns in a neonatal Intensive Care Unit (ICU) in the region of the archipelago of Marajó/PA. This is a qualitative, retrospective study in which a search and analysis of the patient’s chart was carried out. Through speech therapy, qualified assistance can be given to the patient, ensuring safe food, reintroduction of oral feeding and hospital discharge. Thus, the role of the speech therapy in the neonatal and pediatric ICU is of paramount importance, as this professional is an active member of the multidisciplinary team.